Musical Interpretation: a hermeneutics reading - Morais e Silva, Luciano Cesar [UNESP] (Univ Federal Piaui, Editora, 2016)
This article looks for a dialogue between philosophy and music, this threated more like knowledge, than social or aesthetical phenomena. We tried overpassing the Boethius's classification, which quoted the theoretic as the most elevated type of musician, above the instrumentalist and the poet. What this classification lost in its sight is that music - as any artistic proposition - is a form of thought. Gadamer comes here with his Truthand Method, one of the most solids works in epistemology of the twenty century. He determine that art besides philosophy (.) as the most peremptory advise to the scientific consciousness in the sense of recognize its limitations (GADAMER, 2008, p. 33). It is in this key that we developed a preliminary model for musical interpretation. This model needs to be, at the same time, systematic (keeping the control of those prejudices that can be problematic, but not abandoning them while they play a role of structural support to the research) and open (keeping the possibility of recognize the diverse foundations of understanding without deviations of the central object of the research). This has philosophical implications in the social-historical role of the musician/researching. In an approaching like this, it is justified not only the presence of music in the University, but, also the fact - disturbing for some attached to the musikwissenschaft tradition - of this presence give shelter to some models of the conservatory model of learning by practice. This models are not here as an accepted tradition, but as a starting point to news (and self-critical) artistic propositions. In addition, of course, of a solid form of knowledge.
Keywords: Gadamer; hermeneutics; music; musical interpretation